Analysis of influence of ionosphere and troposphere model on RAIM availability of COMPASS - Wei-dong JIAO; Zhi-hu TANG; Xiao-yun SHEN (Tongxin xuebao)
The ionosphere and troposphere are main error sources of satellite navigation system measurement and main factors of COMPASS availability. The influence of the ionosphere and troposphere delay error model on the RAIM availability of COMPASS is analyzed in simulation where ephemeris datum is adopted, and especially the influence of different troposphere models on RAIM availability in civil aviation is analyzed. The experiment at results shows that the delay error of ionosphere and troposphere changes from 0 to 14.555 9 m and 0 to 23.779 6 m correspondingly. And for the non-precision approach stage of civil aviation, when Saastamoinen model, UNB3 model and Hopfield model are used as the troposphere model of COMPASS respectively, the RAIM availability is 99.308%, 92.041 5% and 100% corre-spondingly. So it is more suitable that Hopfield model is used as the troposphere model of COMPASS and the 99.9% RAIM availability requirement in civil aviation can be achieved using this model.